Phytochemical study of Alzatea verticillata, the sole species belonging to the Alzateaceae family - Ferreira Queiroz, Marcos Marçal; Huber, Robin; Marcourt, Laurence; Guénée, Laure; Allard, Pierre-Marie; Rutz, Adriano; Nothias, Louis-Félix; Carlotta De Ruvo, Concetta; Kissling, Jonathan; Gupta, Mahabir Prashad; Ferreira Queiroz, Emerson; Wolfender, Jean-Luc (Frontiers in Natural Products, 2023)
Alzatea verticillata Ruiz & Pav. (Alzateaceae) is a tropical tree from Central and South America. It is the only living species of Alzatea genus and the Alzateaceae family, all others being extinct. With the aim to investigate the possibility to find unusual natural products, the chemical content of the dichloromethane and methanolic extracts (stems and leaves) of A. verticillata have been investigated. Apolar and polar extracts were purified by semi-preparative HPLC using appropriate stationary phase columns allowing the isolation of 12 compounds: walterolactone B (2) walterolactone A/B β-D-pyranoglucoside (3), gallic acid (4), caffeic acid 4-O-β-D-glucopyranoside (6), walterolactone A/B 6-O-gallate-β-D-glucopyranoside (8), caffeic acid (9), 8-desmethylsideroxylin (11), sideroxylin (12) and 7,7′-bis(3,4-dihydroxyphenyl)-8,8′-cyclobutanedicarboxylic acid (7). Three isolated compounds are natural products described here for the first time: dimethyl-anemonin (1) and two β-truxinic acid derivatives (rel-(7S, 8R, 7′R, 8′S)-7,7′-bis(4-glucosyloxy-3-hydroxyphenyl)-8,8′-cyclobutane dicarboxylic acid (5) and rel-(7S, 8R, 7′R, 8′S)-7,7′-bis(4-glucosyloxy-3-hydroxyphenyl)-8,8′-cyclobutane-9-methyl dicarboxylic acid (10). The structures of the isolated compounds were elucidated by NMR and HRMS. The structure of compound 1 was confirmed by X-ray crystallography. A MS-based metabolite analysis of the A. verticillata extracts revealed additional truxinic acid derivatives that were putatively annotated with the help of feature-based molecular network. The presence of phenolic compounds such as truxinic acid derivatives could explain the traditional use of this plant as these compounds are known to possess anti-inflammatory and anti-nociceptive properties.